Mitigation of Traffic Induced Vibration Using Geocell Inclusions - Hegde, Amarnath; Venkateswarlu, Hasthi (Frontiers in Built Environment, 2019)
This paper describes the potential use of geocell reinforcement in mitigating the traffic induced vibration. The vibration caused by the vehicular movement was simulated over the unreinforced and geocell reinforced sections using mechanical oscillator. The displacement amplitude and peak particle velocity were measured to understand the vibration mitigation efficacy of geocell. The effect of depth of placement of geocell on the mitigation of vibration parameters was studied. The inclusion of geocell was found effective in reducing the induced vibration based on the experimental results. The vibration mitigation efficacy of geocell was improved significantly at the shallow depth of placement of geocell mattress. The improvement in elasticity of the subgrade was observed maximum when the geocell was placed at a depth of 0.1B from the ground surface. Further, analytical and numerical approaches were used to predict the displacement amplitude versus frequency response of reinforced soil sections. FLAC3D was used for performing the numerical investigation. The geocell was modelled according to its honeycomb shape to acquire the accurate response of geocell reinforced section. Whereas, mass spring dashpot analogy was followed for the analytical evaluation. In overall, the amplitude response predicted from the numerical and analytical studies were found to be in good agreement with the experimental results.